Iron oxide composite fe s catalyst, preparation method thereof and electro-catalytic denitration method
Patent Information
- Application Number
- CN202611207218.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有电催化体系中,铁基催化剂(零价铁或铁氧化物)表面电子传输阻抗较高,导致活性物种(如OH自由基)生成效率低,NOx脱除率和稳定性难以满足工业需求
[0015] This invention provides an iron oxide composite FeS catalyst, comprising an iron-based core and an FeS shell encapsulating the surface of the iron-based core; the iron-based core comprises iron oxide; or, the iron-based core comprises a transition layer of zero-valent iron and iron oxide. This invention constructs the iron oxide composite FeS (Fe...) in situ via a hydrothermal method. x O y FeS) has a sheet-like structure, with the sheet-like FeS shell serving as an electron transport channel. Furthermore, the high conductivity of FeS reduces electron transport impedance, allowing Fe... x O y The highly reactive iron species (Fe2O3, Fe3O4, and FeO) are more likely to undergo oxidation reactions at the anode, promoting the activation and generation of molecular oxygen and H2O. OH radicals efficiently oxidize NO. xThe use of nitrates solves the problem of insufficient activity in traditional iron-based catalysts. Furthermore, NO... x It is oxidized to nitrate, which can be further purified to nitric acid, realizing the resource utilization of pollutants. As can be seen from the results of the embodiments of this invention, the Fe prepared by this invention... x O y @FeS catalyst for NO x The removal rate can reach over 90%, and the stability is excellent, with no significant decrease in efficiency after 60 hours of continuous reaction.
Smart Images

Figure CN122918628A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of air pollution control technology, specifically relating to an iron oxide composite FeS catalyst, its preparation method, and an electrocatalytic denitrification method. Background Technology
[0002] Nitrogen oxides (NO) x Non-ferrous metal slag is one of the major air pollutants, primarily originating from industrial waste gases from the metallurgical, chemical, and power industries. Its emissions lead to environmental problems such as acid rain and photochemical smog, seriously threatening the ecological environment and human health. Furthermore, the metallurgical and chemical industries produce large quantities of diverse non-ferrous metal smelting waste. This waste is rich in heavy metals and is currently mostly dumped in the open, making resource utilization difficult and posing a pollution threat to the surrounding environment. Therefore, promoting the resource utilization and pollution reduction of non-ferrous metal smelting waste has become a critical issue that urgently needs to be addressed in this industry.
[0003] Electrocatalytic oxidation denitrification technology has become a popular choice for removing NO due to its mild reaction conditions and low secondary pollution. x This is an important research direction. However, in existing electrocatalytic systems, iron-based catalysts (zero-valent iron or iron oxides) have high surface electron transport impedance, leading to limitations in the activity of active species (such as...). The generation efficiency of OH radicals is low, and NO... x The removal rate and stability are insufficient to meet industrial requirements. Therefore, developing an iron-based catalyst that can reduce electron transport impedance and enhance surface electron transfer rate is crucial for improving NO removal efficiency. x Removal efficiency is of great significance. Summary of the Invention
[0004] The purpose of this invention is to provide an iron oxide composite FeS catalyst, its preparation method, and an electrocatalytic denitrification method. This invention reduces electron transport impedance and promotes denitrification by constructing an FeS-modified iron phase interface. OH radicals are generated, achieving efficient and stable denitrification.
[0005] To achieve the objectives of this invention, the following technical solutions are provided: An iron oxide composite FeS catalyst includes an iron-based core and an FeS shell encapsulating the surface of the iron-based core; The iron-based core comprises iron oxide; or, the iron-based core comprises zero-valent iron and an iron oxide transition layer.
[0006] Preferably, the thickness of the FeS shell is 5~200 nm.
[0007] Preferably, the mass ratio of the iron-based core to the FeS shell is 5~100:1.
[0008] This invention also provides a method for preparing the iron oxide composite FeS catalyst described in the above technical solution, comprising the following steps: Iron source, sulfur source and water are mixed and the pH value is adjusted to 2~6 to carry out hydrothermal reaction to obtain the iron oxide composite FeS catalyst; the hydrothermal reaction temperature is 150~220℃ and the time is 6~24h.
[0009] Preferably, the iron source includes one or more of water-soluble iron ion salts, iron oxide species, and reduced iron; The sulfur source is one or more of elemental sulfur, thioacetamide, thiourea, and sodium sulfide.
[0010] Preferably, the reagent used to adjust the pH value is hydrochloric acid or sodium hydroxide solution; the concentration of the hydrochloric acid is 0.1~1 mol / L; the concentration of the sodium hydroxide solution is 0.1~1 mol / L.
[0011] Preferably, the iron oxide species include one or more of Fe2O3, Fe3O4 and FeO.
[0012] This invention provides a method for electrocatalytic denitrification using an electrocatalytic denitrification system, wherein the anode of the electrocatalytic denitrification system is loaded with the iron oxide composite FeS catalyst described in the above technical solution.
[0013] Preferably, the electrolyte in the electrocatalytic denitrification system is a Na2SO4 and / or H2SO4 solution with a pH value of 0.1 to 6.0.
[0014] Preferably, the electrocatalytic denitrification system is introduced with NO. x Gas; the NO x The concentration of NO in the gas is 300~1000ppm; NO x The gas flow rate is 200~500 mL / min.
[0015] This invention provides an iron oxide composite FeS catalyst, comprising an iron-based core and an FeS shell encapsulating the surface of the iron-based core; the iron-based core comprises iron oxide; or, the iron-based core comprises a transition layer of zero-valent iron and iron oxide. This invention constructs the iron oxide composite FeS (Fe...) in situ via a hydrothermal method. x O y FeS) has a sheet-like structure, with the sheet-like FeS shell serving as an electron transport channel. Furthermore, the high conductivity of FeS reduces electron transport impedance, allowing Fe... x O y The highly reactive iron species (Fe2O3, Fe3O4, and FeO) are more likely to undergo oxidation reactions at the anode, promoting the activation and generation of molecular oxygen and H2O. OH radicals efficiently oxidize NO. xThe use of nitrates solves the problem of insufficient activity in traditional iron-based catalysts. Furthermore, NO... x It is oxidized to nitrate, which can be further purified to nitric acid, realizing the resource utilization of pollutants. As can be seen from the results of the embodiments of this invention, the Fe prepared by this invention... x O y @FeS catalyst for NO x The removal rate can reach over 90%, and the stability is excellent, with no significant decrease in efficiency after 60 hours of continuous reaction. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 Fe obtained in Example 1 x O y Scanning electron microscope (SEM) image of FeS sheet catalyst. Figure 2 Fe obtained in Example 1 x O y @FeS sheet catalyst and Fe x O y The electron transport impedance spectrum; Figure 3 Fe obtained in Example 1 x O y @FeS sheet catalyst for electrocatalytic oxidation of NO x The efficiency curve. Detailed Implementation
[0018] This invention provides an iron oxide composite FeS catalyst, comprising an iron-based core and an FeS shell encapsulating the surface of the iron-based core; The iron-based core comprises iron oxide; or, the iron-based core comprises zero-valent iron and an iron oxide transition layer.
[0019] In this invention, unless otherwise specified, all raw materials used in the preparation are commercially available products well known to those skilled in the art.
[0020] In this invention, the iron source includes one or more of soluble iron ion salts, iron oxide species, and reduced iron; the soluble iron ion salt can be one or more of ferric nitrate, ferric sulfate, ferrous sulfate, ferrous chloride, and ferric chloride; in this invention, the thickness of the FeS shell is 5~200 nm, and in specific embodiments it can be 10, 20, 50, 80, or 120 nm.
[0021] In this invention, the mass ratio of the iron-based core to the FeS shell is 5 to 100:1, and in specific embodiments it can be 10:1, 25:1, 40:1 or 60:1.
[0022] In this invention, the iron oxide composite FeS catalyst has a sheet-like structure with a thickness of 50~1000nm, which can be 70, 200 or 500, 800nm in specific embodiments.
[0023] This invention also provides a method for preparing the iron oxide composite FeS catalyst described in the above technical solution, comprising the following steps: Iron source, sulfur source and water are mixed and the pH value is adjusted to 2~6 to carry out hydrothermal reaction to obtain the iron oxide composite FeS catalyst; the hydrothermal reaction temperature is 150~220℃ and the time is 6~24h.
[0024] In this invention, the iron source includes one or more of water-soluble iron ion salts, iron oxide species, and reduced iron, wherein the iron oxide species include one or more of Fe2O3, Fe3O4, and FeO.
[0025] In this invention, the iron oxide species are derived from commercially available sources or prepared using the following methods: The iron-containing waste slag is prepared by calcination; or by calcination of iron-containing waste slag and a reducing agent. The iron-containing waste slag in this invention includes one or more of copper slag, lead-zinc slag, steel slag, manganese slag, and red mud; the iron content in the iron-containing waste slag is ≥10wt%, specifically 10~45wt%, and in specific embodiments, it can be 15wt%, 18wt%, 23wt%, 25wt%, 38wt%, or 30wt%; the reducing agent can be carbon powder, and the mass of the reducing agent is 50~500wt% of the mass of the iron waste slag, and in specific embodiments, it can be 100wt%; the calcination temperature is 900~1200℃, and the time is 1~3h. In specific embodiments of this invention, the iron oxide species can be copper slag-based reduced iron powder or manganese slag-based iron oxide.
[0026] In this invention, the copper slag comprises Fe2SiO4, Fe3O4, and SiO2, with an iron content of 15-45 wt%, and originates from the matte smelting or converter blowing stage in the pyrometallurgical copper smelting process; the manganese slag comprises Fe2O3, FeO, SiO2, and MnO, with an iron content of 10-25 wt%, and originates from the leaching residue of silicon-manganese alloy smelting or electrolytic manganese metal; the red mud comprises Fe2O3 and Al2O3, with an iron content of 25-45 wt%, and originates from the tailings after alumina extraction from bauxite using the Bayer process; the steel slag comprises Fe2O3, FeO, CaO, and SiO2, with an iron content of 15-30 wt%, and originates from the slag discharge stage of converter or electric arc furnace steelmaking; the lead-zinc slag comprises FeO, Fe3O4, SiO2, and ZnO, with an iron content of 25-40 wt%, and originates from the blast furnace and oxygen-enriched bottom-blown smelting stages in the pyrometallurgical lead-zinc smelting process.
[0027] In this invention, the sulfur source is one or more of elemental sulfur, thioacetamide (TAA), thiourea (CH4N2S), and sodium sulfide (Na2S), and the elemental sulfur can be sublimed sulfur; the molar ratio of sulfur in the sulfur source to iron in the iron source is 1~5:1, and in specific embodiments it can be 2:1 or 3:1.
[0028] In this invention, the reagent used to adjust the pH value is hydrochloric acid or sodium hydroxide solution; the concentration of the hydrochloric acid is 0.1~1 mol / L, and in a specific embodiment it can be 0.3 or 0.5 mol / L; the concentration of the sodium hydroxide solution is 0.1~1 mol / L, and in a specific embodiment it can be 0.5 or 0.8 mol / L.
[0029] In this invention, the temperature of the hydrothermal reaction is 150~220℃, and in specific embodiments it can be 160, 180 or 200℃, and the time is 6~24h, and in specific embodiments it can be 8, 12 or 12h; the hydrothermal reaction is carried out in a reaction vessel.
[0030] In this invention, within a high-temperature, high-pressure hydrothermal system, water molecules themselves exhibit a certain degree of weak oxidizing property. Combined with the unavoidable residual dissolved oxygen within the reactor, this process promotes the in-situ oxidation of zero-valent iron during the hydrothermal process, resulting in the formation of Fe on the surface. x O y Fe was obtained first x O y The core and transition of Fe on the surface of the zero-valent iron substrate x O y Fe layer x O y Kernel.
[0031] When water-soluble iron salts are used as the iron source, under hydrothermal conditions and an acidic environment with a pH of 2-6, the soluble iron ions in the system will preferentially undergo hydrolysis and condensation reactions to generate Fe. x O y (Or precursor FeOOH) nanonuclei, i.e., hydrothermal in-situ growth and nucleation reaction. Subsequently, the surface of the nanonuclei undergoes an in-situ sulfidation reaction with oxide species released in the system, generating an FeS shell. Specifically, during the hydrothermal process, the sulfur source undergoes disproportionation or reduction reactions under high temperature, high pressure, and specific pH conditions, slowly releasing active sulfur species (such as H2S, S2). - When the iron source is a water-soluble iron ion salt, the iron salt first hydrolyzes into nuclei in high-temperature water, generating FexOy or iron hydroxyl oxide (FeOOH) nanoparticles. The surface of the newly formed nanoparticles has high reactivity, which then reacts with the released H2S or S2. - The reaction results in in-situ sulfidation of the surface, forming a lamellar FeS shell. When the iron source is iron oxide, the iron oxide species undergo slight etching and dissolution on the surface in an acidic (pH 2-6) hydrothermal environment, releasing a small amount of iron ions. These free iron ions recombine with sulfur species on the undissolved iron oxide substrate surface, nucleating in situ and epitaxially growing a lamellar FeS layer. When the iron source is reduced iron, the reduced iron surface undergoes slight hydrogen evolution corrosion under high-temperature water and acidic conditions, releasing Fe... 2+ This creates a localized weakly reducing environment for Fe. 2+ By reacting with sulfur species, well-formed nanopetal-shaped FeS shells are assembled and grown on zero-valent iron substrates or on their extremely thin oxide layers.
[0032] After the hydrothermal reaction is completed, the present invention further includes centrifugation, washing and drying; the washing is performed by washing with deionized water and ethanol 1 to 3 times respectively; the drying temperature is 60 to 100°C and the time is 6 to 12 hours.
[0033] The present invention also provides a method for electrocatalytic denitrification using an electrocatalytic denitrification system, wherein the anode of the electrocatalytic denitrification system is loaded with the iron oxide composite FeS catalyst described in the above technical solution.
[0034] In this invention, the anode can be a carbon paper electrode; this invention does not have any special limitations on the loading method of the iron oxide composite FeS catalyst and the electrode, and in specific embodiments it can be coating.
[0035] In this invention, the applied voltage in the electrocatalytic denitrification system is 0.6~1.5V, and in specific implementations it can be 0.8 or 1.2V.
[0036] In this invention, the electrolyte in the electrocatalytic denitrification system is a Na2SO4 and / or H2SO4 solution with a concentration of 0.1~1 mol / L. The electrolyte in this invention can be Na2SO4 with a concentration of 0.1~1 mol / L, or H2SO4 with a concentration of 0.1~1 mol / L, or Na2SO4 and H2SO4 with concentrations of 0.1~1 mol / L respectively. In specific implementations, it can be 0.5 or 0.8 mol / L, and the pH value is 0.1~6. In specific implementations, it can be 0.5, 1, 3 or 4.
[0037] In this invention, the electrocatalytic denitrification system is introduced with NO. x Gas; NO x The concentration of NO in the gas is 300~1000 ppm, and in specific embodiments it can be 500, 600, 700 or 800 ppm; NO x The gas flow rate is 200~500mL / min, and in specific embodiments it can be 250, 300 or 350mL / min.
[0038] To further illustrate the present invention, the iron oxide composite FeS catalyst, its preparation method, and the electrocatalytic denitrification method provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0039] Example 1 Copper slag (containing olivine Fe2SiO4 and magnetite Fe3O4, with an iron content of approximately 23-30 wt%) was crushed and ball-milled to 200 mesh. Copper slag was mixed with 30 wt% carbon powder (carbon content greater than 60%), and the mixture was placed in a tube furnace and calcined at 1100℃ for 2 hours under a nitrogen atmosphere at a rate of 5℃ / min. After natural cooling, the product was collected, ball-milled again to 200 mesh, and then magnetically separated to obtain copper slag-based reduced iron powder (iron content ≥85%). Weigh 2g of the above copper slag-based reduced iron powder and 2g of sublimed sulfur, add 50mL of deionized water, and stir magnetically for 30min until completely dissolved. Adjust the pH of the mixture to 3 with 0.1mol / L hydrochloric acid. Transfer the mixture to a 100mL hydrothermal reactor and react hydrothermally at 160℃ for 15h. After cooling to room temperature, centrifuge to separate the product, wash three times each with deionized water and ethanol, and dry at 80℃ for 10h to obtain Fe. x O y @FeS sheet catalyst.
[0040] Fe x O yFeS sheet catalyst coated on carbon paper was used as the anode and placed in a 0.5 mol / L Na2SO4 electrolyte (pH=6). A voltage of 2.0 V was applied, and simulated tail gas with NOx (NO concentration 500 ppm) was introduced (flow rate 300 mL / min). Denitrification was performed at 30 °C. The NO removal rate was 85%, and it remained at 78% after 50 hours of continuous reaction.
[0041] Figure 1 Fe obtained in Example 1 x O y Scanning electron microscopy (SEM) image of the FeS sheet-like catalyst. The results show that Fe... x O y @FeS exhibits a plate-like morphology, with a core consisting of zero-valent iron and Fe. x O y The composite core of the iron oxide transition layer is FeS, and the outer shell is FeS.
[0042] Figure 2 Fe obtained in Example 1 x O y @FeS sheet catalyst and Fe x O y The electron transport impedance spectrum indicates that Fe x O y The impedance of @FeS is significantly lower than that of pure Fe. x O y ; Figure 3 Fe obtained in Example 1 x O y @FeS sheet catalyst for electrocatalytic oxidation of NO x The efficiency curve shows that Fe x O y @FeS sheet catalysts exhibit high stability.
[0043] Example 2 Weigh 2g of commercially available analytical grade 200-mesh reduced iron powder and 3g of sublimed sulfur, add 100mL of deionized water, and stir magnetically for 15min until completely dissolved. Adjust the pH of the mixture to 5 with 0.1mol / L hydrochloric acid. Transfer the mixture to a 200mL hydrothermal reactor and react at 160℃ for 15h. After cooling to room temperature, centrifuge to separate the product, wash three times each with deionized water and ethanol, and dry at 60℃ for 10h to obtain Fe. x O y @FeS sheet catalyst.
[0044] Fe x O yFeS sheet catalyst coated on carbon paper was used as the anode and placed in a 0.5 mol / L Na2SO4 electrolyte (pH=6). A voltage of 1.8V was applied, and NO was introduced. x Simulated exhaust gas (NO concentration 800 ppm) at a flow rate of 300 mL / min was denitrified at 25°C. The NO removal rate was 90%, and it remained at 85% after 50 hours of continuous reaction.
[0045] Example 3 Weigh 2g of steel slag, 0.05mol of ferric nitrate, and 0.1mol of sublimed sulfur, add 50mL of deionized water, stir well, adjust the pH to 5 with 0.1mol / L sodium hydroxide, and hydrothermally react at 180℃ for 12h. After cooling to room temperature, centrifuge to separate the product, wash three times each with deionized water and ethanol, and dry at 80℃ for 10h to obtain Fe. x O y @FeS sheet catalyst; Electrocatalytic denitrification was carried out according to the steps in Example 1, with a NO removal rate of 83% and a removal rate of 70% after continuous reaction for 50 hours.
[0046] Example 4 Manganese slag was crushed and ball-milled to 200 mesh, then fed into a muffle furnace and calcined at 900°C for 2 hours under an air atmosphere with a continuous heating rate of 5°C / min. After natural cooling, it was collected and ball-milled to 200 mesh to obtain manganese slag-based iron oxide. Weigh 2g of manganese slag-based iron oxide and 4g of sublimed sulfur, add 100mL of deionized water, and stir magnetically for 15min until completely dissolved. Adjust the pH of the mixture to 5 with 0.1mol / L hydrochloric acid. Transfer the mixture to a 200mL hydrothermal reactor and react hydrothermally at 180℃ for 15h. After cooling to room temperature, centrifuge to separate the product, wash three times each with deionized water and ethanol, and dry at 80℃ for 10h to obtain Fe. x O y @FeS sheet catalyst.
[0047] The obtained Fe x O y @FeS sheet catalyst coated on carbon paper as the anode, in 0.5 mol / L Na2SO4 electrolyte (pH=6), a voltage of 1.5V is applied, and simulated tail gas with NOx (NO concentration of 500 ppm) is introduced (flow rate of 300 mL / min). Denitrification is carried out at 25℃, and the NO removal rate is 80%. After continuous reaction for 50 h, the removal rate still remains at 69%.
[0048] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An iron oxide composite FeS catalyst, characterized in that, It includes an iron-based core and an FeS shell that wraps around the surface of the iron-based core; The iron-based core comprises iron oxide; or, the iron-based core comprises zero-valent iron and an iron oxide transition layer.
2. The iron oxide composite FeS catalyst according to claim 1, characterized in that, The thickness of the FeS shell is 5~200nm.
3. The iron oxide composite FeS catalyst according to claim 1, characterized in that, The mass ratio of the iron-based core to the FeS shell is 5~100:
1.
4. The method for preparing the iron oxide composite FeS catalyst according to any one of claims 1 to 3, characterized in that, Includes the following steps: Iron source, sulfur source and water are mixed and the pH value is adjusted to 2~6 to carry out hydrothermal reaction to obtain the iron oxide composite FeS catalyst; the hydrothermal reaction temperature is 150~220℃ and the time is 6~24h.
5. The preparation method according to claim 4, characterized in that, The iron source includes one or more of water-soluble iron ion salts, iron oxide species, and reduced iron. The sulfur source is one or more of elemental sulfur, thioacetamide, thiourea, and sodium sulfide.
6. The preparation method according to claim 4, characterized in that, The reagent used to adjust the pH value is hydrochloric acid or sodium hydroxide solution; the concentration of the hydrochloric acid is 0.1~1 mol / L; the concentration of the sodium hydroxide solution is 0.1~1 mol / L.
7. The preparation method according to claim 5, characterized in that, The iron oxide species include one or more of Fe2O3, Fe3O4 and FeO.
8. A method for electrocatalytic denitrification using an electrocatalytic denitrification system, characterized in that, The anode in the electrocatalytic denitrification system is supported by the iron oxide composite FeS catalyst according to any one of claims 1 to 3.
9. The electrocatalytic denitrification method according to claim 8, characterized in that, The electrolyte in the electrocatalytic denitrification system is a Na2SO4 and / or H2SO4 solution with a pH value of 0.1~6.
0.
10. The electrocatalytic denitrification method according to claim 8, characterized in that, The electrocatalytic denitrification system introduces NO x Gas; the NO x The concentration of NO in the gas is 300~1000ppm; NO x The gas flow rate is 200~500 mL / min.